BASIC CALCULATIONS FOR THE DETERMINATION OF LIFE OF A LANDFILL - Loayza Pérez, Jorge Eduardo (2006)
A landfill is an infrastructure used for the final disposal of non-recyclable wastes. lt is possible to calculate its usetul lifetime by taking into account three cases; the first one assumes that there is no growth in the population, the second that the population doubles every given number of years and the third that the population grows exponentially. The following article presents all three cases in detail; as well as examples to determine the useful lifetime of the landfill (in years).